The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s0101-31222010000200009
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da irrigação sobre o potencial fisiológico de sementes de soja em semeadura de inverno

Abstract: 1RESUMO -Período seco e temperaturas amenas são condições climáticas ideais durante a maturação e colheita de sementes de soja. O objetivo foi verificar o efeito da irrigação no período pós-maturidade fisiológica, sobre o potencial fisiológico de sementes de soja semeadas no inverno. A disposição dos tratamentos seguiu esquema fatorial envolvendo três cultivares (IAC-19, Conquista e IAC 8-2) e duas épocas de interrupção da irrigação (início do estádio R 7 e irrigação até 14 dias após R 8 ). Foram feitas amostr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(18 reference statements)
1
0
0
2
Order By: Relevance
“…In water stress in all phases (W5), reduction in performance of seeds was more intense for SE ( Table 2); similar to the results obtained for the variables seedling fresh weight (SFW) and seedling dry weight (SDW). This result can be attributed to the occurrence of a water restriction during the development period of the seeds, which may have affected the deposition of reserves, the proper formation of cell membranes and the correct establishment of the hydrolytic enzyme system of the seeds [27]. Our results corroborate Silva et al [9] who showed that there was a reduction in the physiological quality of the seeds of sesame when comparing treatments in stress throughout the cycle and in full irrigation.…”
Section: Discussionsupporting
confidence: 89%
“…In water stress in all phases (W5), reduction in performance of seeds was more intense for SE ( Table 2); similar to the results obtained for the variables seedling fresh weight (SFW) and seedling dry weight (SDW). This result can be attributed to the occurrence of a water restriction during the development period of the seeds, which may have affected the deposition of reserves, the proper formation of cell membranes and the correct establishment of the hydrolytic enzyme system of the seeds [27]. Our results corroborate Silva et al [9] who showed that there was a reduction in the physiological quality of the seeds of sesame when comparing treatments in stress throughout the cycle and in full irrigation.…”
Section: Discussionsupporting
confidence: 89%
“…De maneira geral a qualidade inicial das sementes não foi influenciada pelos sistemas de cultivo, sendo que foi verificada pequena diferença de qualidade entre os lotes estudados, por sua vez Silva et al (2005) Os efeitos do vigor das sementes sobre o desempenho das plantas podem ser evidentes no início do desenvolvimento, mas são reduzidos à medida que os estádios fenológicos se sucedem (Carvalho, 1986). Para TeKrony & Egli (1991) a influência do vigor de sementes no estabelecimento do estande pode ser especialmente crítica para culturas que requerem distribuição espacial de plantas para maximizar o rendimento como alface, repolho, cebola e couve-flor.…”
Section: Resultado E Discussãounclassified
“…outubro e novembro, com colheita entre fevereiro e abril (SILVA et al, 2010). Entretanto, épocas de semeadura distintas das tradicionais têm sido estudadas visando rotação de culturas e melhor aproveitamento da terra tanto em terras altas com uso de irrigação por aspersão (CRUSCIOL, et al, 2002;SILVA et al, 2010), quanto em várzea irrigada, com elevação do lençol freático ( PELUZIO et al, 2010;ALMEIDA et al, 2011), esta pratica de cultivo (entressafra) traz enormes benefícios a próxima cultura, Brancalião et al (2015) comprovou efetivas diferenças positivas na produtividade de soja em sucessão a outra cultura em relação ao pousio.…”
unclassified